Different systolic blood pressure targets for people with history of stroke or transient ischaemic attack: PAST-BP (Prevention After Stroke—Blood Pressure) randomised controlled trial. (24th February 2016) - Mant, Jonathan; McManus, Richard J; Roalfe, Andrea; Fletcher, Kate; Taylor, Clare J; Martin, Una; Virdee, Satnam; Greenfield, Sheila; Hobbs, F D Richard
Abstract : Objective  To assess whether using intensive blood pressure targets leads to lower blood pressure in a community population of people with prevalent cerebrovascular disease. Design  Open label randomised controlled trial. Setting  99 general practices in England, with participants recruited in 2009-11. Participants  People with a history of stroke or transient ischaemic attack whose systolic blood pressure was 125 mm Hg or above. Interventions  Intensive systolic blood pressure target (<130 mm Hg or 10 mm Hg reduction from baseline if this was <140 mm Hg) or standard target (<140 mm Hg). Apart from the different target, patients in both arms were actively managed in the same way with regular reviews by the primary care team. Main outcome measure  Change in systolic blood pressure between baseline and 12 months. Results  529 patients (mean age 72) were enrolled, 266 to the intensive target arm and 263 to the standard target arm, of whom 379 were included in the primary analysis (182 (68%) intensive arm; 197 (75%) standard arm). 84 patients withdrew from the study during the follow-up period (52 intensive arm; 32 standard arm). Mean systolic blood pressure dropped by 16.1 mm Hg to 127.4 mm Hg in the intensive target arm and by 12.8 mm Hg to 129.4 mm Hg in the standard arm (difference between groups 2.9 (95% confidence interval 0.2 to 5.7) mm Hg; P=0.03). Conclusions  Aiming for target below 130 mm Hg rather than 140 mm Hg for systolic blood pressure in people with cerebrovascular disease in primary care led to a small additional reduction in blood pressure. Active management of systolic blood pressure in this population using a <140 mm Hg target led to a clinically important reduction in blood pressure. Trial registration  Current Controlled Trials ISRCTN29062286 .